Delayed Onset of Thrombotic Microangiopathy (TMA) upon Prolonged Carfilzomib Therapy in Multiple Myeloma: A Case Report and Comprehensive Review - Andrea Ceglédi; Ágnes Király; Andrea Várkonyi; Szabolcs Tasnády; Hajnalka Andrikovics; Mónika Fekete; Bálint G. Szabó; Zsuzsanna Szemlaky; Ágnes Szilágyi; György Sinkovits; Zoltán Prohászka; Marienn Réti; et al. (Pharmaceuticals)
Background: Thrombotic microangiopathy (TMA) is a potentially life-threatening complication associated with carfilzomib, a proteasome inhibitor approved for treating multiple myeloma. TMA typically presents within the initial months of treatment; however, delayed onset is rare and poses significant diagnostic challenges. Methods: We conducted a retrospective analysis of the medical records of a 47-year-old Caucasian woman diagnosed with IgA kappa myeloma who developed signs and symptoms consistent with TMA eleven months after the initiation of carfilzomib therapy and already in ongoing very good partial remission. Results: The clinical presentation included an acute onset of weakness, dizziness, somnolence, diffuse bruising, oliguria, jaundice, severe thrombocytopenia, and acute kidney injury. An immediate workup raised a strong suspicion for TMA, confirmed by laboratory findings of schistocytosis and complement activation. Following the immediate discontinuation of carfilzomib, the patient underwent 18 plasmapheresis (PEX) sessions and received supportive fresh frozen plasma transfusions, which resulted in the complete remission of TMA symptoms without the need for complement inhibitory therapy. Conclusions: The need for ongoing monitoring for TMA throughout carfilzomib therapy, regardless of treatment duration, is emphasized. Early diagnosis and intervention, including drug discontinuation and the timely initiation of PEX, are crucial for patient recovery.